2008
DOI: 10.1002/jsfa.3393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibrolytic enzymes and an inoculant on in vitro degradability and gas production of low‐dry matter alfalfa silage

Abstract: BACKGROUND: The objective of this study was to investigate the effect of polysaccharide-degrading enzymes (a cellulase and a xylanase) alone or in a combination with a bacterial inoculant on fermentation parameters and in vitro degradability and gas production of low-dry matter (DM) alfalfa silage. First cut alfalfa (Medicago sativa L.), harvested at about 5% bloom stage [260 g kg −1 dry matter (DM)] was ensiled in laboratory-scale silos without preservatives or preserved with formic acid, a cellulase (Cell), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
4
33
0
1
Order By: Relevance
“…The similar results were also reported by Muck et al (2007) and Contreras-Govea et al (2013). On the other hand, Kozelov et al (2008) and Denek et al (2011) found that bacterial inoculant increased GP and decreased the GP rate of lucerne silage. In vitro GP, degradation rate and VFA production were higher for high-WSC vs normal-WSC cultivars of sorghum (Amer et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The similar results were also reported by Muck et al (2007) and Contreras-Govea et al (2013). On the other hand, Kozelov et al (2008) and Denek et al (2011) found that bacterial inoculant increased GP and decreased the GP rate of lucerne silage. In vitro GP, degradation rate and VFA production were higher for high-WSC vs normal-WSC cultivars of sorghum (Amer et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…GP, measured manually or automatically, can be treated as a very good indirect indicator of fermentation kinetics (Rymer et al, 2005). Kozelov et al (2008) noted that GP was significantly increased when lucerne was treated with 4 l · t −1 formic acid before ensiling. In the present study, GP of formic acid treated silage was increased by 13.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For barley crop silage (Hristov & McAllister, 2002), all three types of inoculants used, could reduce the silage pH on wilted crop, but two thirds of inoculants were ineffective on unwilted crops. Furthermore, Sheperd et al (1995), Filya et al (2007) and Kozelov et al (2008) observed a lower pH in silages treated with microbial inoculants. It may be attributed to the lower production of ammonia-N and acetate as well as their lower buffering effects in inoculated silages.…”
Section: Discussionmentioning
confidence: 95%
“…Ensilability of alfalfa can be enhanced by conventional approaches, such as utilization of fibrolytic enzymes and additives rich in sugar (Sheperd et al 1995;Wu and Nishino 2016), wilting (Krawutschke et al 2013) and use of lactic acid bacteria (LAB) and short-chain organic acids or salts (Nagel and Broderick 1992;Krawutschke et al 2013;Wen et al 2017). Additives such as cellulase and molasses are often costly commercially and impracticable for dairy farms; in addition, application of them sometimes did not have a remarkable effect on the fermentation properties of alfalfa silage (Kozelov et al 2008;Hashemzadeh-Cigari et al 2014;Lyncha et al 2014). Therefore, development of a new strategy to solve the problem of difficult ensiling is of importance for alfalfa.…”
Section: Introductionmentioning
confidence: 99%